SOLO THE SPIRIT OF JAVA (Studi Deskriptif Kualitatif tentang Strategi Komunikasi Pemasaran Dinas Kebudayaan dan Pariwisata Kota Surakarta slogan Solo The Spirit Of Java dalam Mempertahankan Daya Tarik Kota Solo kepada Wisatawan) - Nurnawati H.H, Ginoviva Tende Nilawati, Bedjo Sukarno & (Transformasi, 2016)
Lots of potential in the city of Solo as tourist places and events that can be enjoyed by thetourists. But in this case, in the process of tourism potential, this work is not an easy task. Thepurpose of this research is to describe and learn about marketing communication strategyundertaken by the Department of culture and tourism city of Surakarta in maintaining theattractiveness of the city of Solo to tourists. Departing from the concept thought theoryMarketing Communication Mix from Ilham Prisgunanto applied on the marketingcommunication strategy includes advertising, public relation, sales promotion, personal selling.This research uses qualitative descriptive research. Location research in the Office Culture andTourism Department city of Surakarta. In this research, researcher used a purposive samplingtechnique as a method in the selection of informants. The results showed that themarketing communication strategy undertaken Disbudpa among others through print media inthe form of banners, billboards, leaflets, booklets, electronic media be videotron, television, andonline media in the form of a Solo Destination application, website. Disbudpar fostering andgiving support perpetrators of the tourist industry in order that the concept of the show ispackaged in quality and taste for tourists to visit in the city of Solo. Disbudpar also promote itsproducts by following the exhibition, send ambassador of art to perform outside of the region.Marketing communications strategy conducted by Disbudpar has maintained the appeal of Solocity to tourists. The slogan of The Solo Spirit Of Java is not only reflected in the show, butalso on the services, as well as showing the community the city of Solo.Key word: Marketing Communication Strategy and Attraction of Solo City